Increasing Knowledge Through Anemia Discussion, Hemoglobin (Hb) Skrinning and COVID-19 Vaccines in Young Women - Astriani, Ranti Dwi; Nuraeni, Hanny Siti; Shufiyani, Shufiyani (Jurnal Menara Pengabmas, 2023)
The problem in this community service activity is the lack of understanding about anaemia among adolescent girls in Global Mansion Housing, Periuk Village, Tangerang City. According to data from the Tangerang City portal, the achievement of COVID-19 vaccination in Periuk urban village is still low (<40%). This should certainly be a common concern, because vaccination is being intensified by the government to prevent and reduce the risk of spreading the COVID-19 virus. Based on WHO 2010, the prevalence of anaemia among adolescent girls in developing countries is around 53.7% of all adolescent girls. According to Riskesdas 2018, anaemia in adolescent girls aged 13-18 years in Indonesia is still high at 22.7%. The purpose of this community service is to provide an understanding of anaemia prevention and the COVID19 vaccine to reduce the spread of the COVID-19 virus. Community service activities are carried out offline by conducting counselling in the form of presentations, brochures, questions and answers, pre-and post-test with adolescent girls and parents. During the activity, participants can follow well, easily understand and engage in discussions. The conclusion of this activity is that there is a significant increase in understanding of anaemia and the COVID-19 vaccine in adolescent girls (30%).